Analysis of Maternal and Child Health Book Utilization Among Pregnant Women - Dina Putriati; Lilis Suryani; Chairil Zaman (Lentera Perawat, 2025)
The Maternal and Child Health (MCH) Book is a vital tool for monitoring maternal health during pregnancy, childbirth, postpartum, and child growth. However, its utilization remains suboptimal in many areas. This study aims to analyze the factors affecting the utilization of the MCH Book among pregnant women at Rawa Bening Health Center, East Ogan Komering Ulu Regency. This research employed a quantitative analytical survey method with a cross-sectional approach. The sample consisted of 93 pregnant women selected through purposive sampling. Data were collected through questionnaires and analyzed using the Chi-Square test. The results showed that age (p = 0.04; OR = 3.08), knowledge (p = 0.002; OR = 5.52), family support (p = 0.03; OR = 2.8), and health worker support (p = 0.04; OR = 3.58) were significantly related to MCH Book utilization. Meanwhile, parity, education, and occupation were not significantly related. Knowledge was the most dominant factor influencing MCH Book utilization. In conclusion, efforts to enhance MCH Book utilization should focus on improving pregnant women's knowledge and the social support they receive.